Rac1 Guides Porf-2 to Wnt Pathway to Mediate Neural Stem Cell Proliferation - Yang, Xi-Tao; Huang, Guo-Hui; Li, Hong-Jiang; Sun, Zhao-Liang; Xu, Nan-Jie; Feng, Dong-Fu (Frontiers in Molecular Neuroscience, 2017)
The molecular and cellular mechanisms underlying the anti-proliferative effects of preoptic regulator factor 2 (Porf-2) on neural stem cells (NSCs) remain largely unknown. Here, we found that Porf-2 inhibits the activity of ras-related C3 botulinum toxin substrate 1 (Rac1) protein in hippocampus-derived rat NSCs. Reduced Rac1 activity impaired the nuclear translocation of β-catenin, ultimately causing a repression of NSCs proliferation. Porf-2 knockdown enhanced NSCs proliferation but not in the presence of small molecule inhibitors of Rac1 or Wnt. At the same time, the repression of NSCs proliferation caused by Porf-2 overexpression was counteracted by small molecule activators of Rac1 or Wnt. By using a rat optic nerve crush model, we observed that Porf-2 knockdown enhanced the recovery of visual function. In particular, optic nerve injury in rats led to increased Wnt family member 3a (Wnt3a) protein expression, which we found responsible for enhancing Porf-2 knockdown-induced NSCs proliferation. These findings suggest that Porf-2 exerts its inhibitory effect on NSCs proliferation via Rac1-Wnt/β-catenin pathway. Porf-2 may therefore represent and interesting target for optic nerve injury recovery and therapy.